A Terapia Expressiva como estratégia de Cuidado Integral no Núcleo de Atenção Oncológica do Hospital Universitário Antônio Pedro - Vianna, Denise (2013)
This dissertation evaluates, through the Action Research method, the effects of Life Infusion (AIV) collective sessions of Expressive Therapy during chemotherapy sessions on the feelings and sense of comfort for those with cancer and several degenerative diseases at the Center for Oncology Care (NAO) of the University Hospital Antonio Pedro . The AIV is the field work of the main action of the extension program Expressive Therapy as a vehicle for Comprehensive Care at the University Hospital Antonio Pedro, extension course Taking Care of Yourself With Art, aimed to promoting a better life quality and care provided by the health professionals. The Expressive Therapy tool, offered to patients, families and caregivers, is conveyed by expressive material, under the Analytical Psychology framework. We evaluated, under triangulation methods by the qualitative and quantitative researches, 413 attendances to 282 patients who attended the 48 sessions between April 5 and November 3, 2011. Data from the interviews were statistically analyzed and contextualized into the themes and categories that emerged during the analysis of the narratives of the open interviews and testimonies recording, and from the field diaries notes made by the members of the program multidisciplinary team, course students and several undergraduate students under the interpretive framework of Social Sciences. The AIV actions were capable of renew patient s perspectives and coping skills, the expression of their emotions and other psychic contents, providing benefits at the physical and spiritual levels, and opportunities to reflect about: their lives trajectory, needs, skills, the present and future prospects. The AIV also contributed to promote more friendly relations between patients and hospital staff, creating a more welcoming atmosphere in the NAO. From the participants descriptions, ongoing research targets, the patients' opinion about the activities and their suggestions and criticisms on the AIV, we could identified questions and solutions related to the humanization and completeness of the hospital's sector where the actions take place, providing a model for the whole hospital and health in general, showing that the proposed model can be applied to other services and hospitals as a new form of complementary care.